1997
DOI: 10.1152/ajpregu.1997.272.1.r208
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous vasoconstriction in conscious rabbits during alerting responses detected by hippocampal theta-rhythm

Abstract: We determined whether alerting stimuli cause cutaneous vasoconstriction in conscious rabbits. We compared ear blood flow with renal, mesenteric, and femoral flows at rest and in response to nonnoxious alerting stimuli, which induced theta-rhythm (4-9 Hz) in the simultaneously recorded hippocampal electroencephalogram (EEG). theta-Inducing stimuli (e.g., whistles and fur touches) reduced ear flow by 95 +/- 6%, commencing 1-2 s after the EEG change and lasting 45 s. Renal flow did not significantly change with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
66
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 0 publications
8
66
0
Order By: Relevance
“…Consistent with this, alerting stimuli in humans reliably increase cutaneous sympathetic activity (156). Brief alerting stimuli also evoke variable and often biphasic changes in heart rate (1,8,33,161) due to the fact that there is coactivation of cardiac sympathetic and vagal parasympathetic activity (1,8,33,123).…”
Section: Pattern Of Cardiovascular and Respiratory Responses To Stresmentioning
confidence: 68%
See 1 more Smart Citation
“…Consistent with this, alerting stimuli in humans reliably increase cutaneous sympathetic activity (156). Brief alerting stimuli also evoke variable and often biphasic changes in heart rate (1,8,33,161) due to the fact that there is coactivation of cardiac sympathetic and vagal parasympathetic activity (1,8,33,123).…”
Section: Pattern Of Cardiovascular and Respiratory Responses To Stresmentioning
confidence: 68%
“…In animals, brief alerting stimuli such as an unexpected noise or light will evoke immediate autonomic and respiratory responses, characterized by strong cutaneous vasoconstriction and respiratory activation (17,18,84,109,161). In contrast, such nonnoxious brief stimuli evoke only small and transient increases in arterial pressure and little or no changes in blood flow to the mesenteric, renal, and hindlimb vascular beds (109,162), indicating that the sympathetic outflow to the cutaneous vascular bed is rather selectively activated by mild alerting stimuli.…”
Section: Pattern Of Cardiovascular and Respiratory Responses To Stresmentioning
confidence: 99%
“…In five rabbits additional blood flow probes were implanted around the facial artery (model 1PSB, Transonic Systems), proximal to the origin of the masseteric artery (35) and around the central ear artery (model 1PSL Transonic Systems), which supplies an almost exclusively cutaneous vascular bed (51).…”
Section: Methodsmentioning
confidence: 99%
“…We then used this protocol to demonstrate that the accompanying hypotension was due to the induced bradycardia. Orienting stimuli are usually reported to induce hypotension and bradycardia, but hypertension and bradycardia have also been noted (19)(20)(21)(22)24,(26)(27)(28)(29)(30). Previous studies have been limited by poorly controlled stimuli, such as a hand clap, which rabbits rapidly learn to ignore (21), and these studies did not report beat-to-beat responses.…”
Section: Discussionmentioning
confidence: 99%
“…We considered three possibilities: that the measured hypotension was a factitious finding due to dampened arterial waveforms associated with proximal ear artery vasoconstriction; the measured hypotension is due to vasodilation; and that the measured hypotension simply reflects a reduction in the calculated MAP due to the protracted diastole brought about by the abrupt bradycardia. Yu and Blessing (24,29,30) reported that rabbits exposed to alerting stimuli, such as brief noises, had central ear artery constriction and reduced flow distal to subacutely implanted flow probes. This vasoconstriction suggests that the apparent hypotension we observed might have been caused by dampened traces distal to localized vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%